IPTEKS PERHITUNGAN PAJAK PENGHASILAN (PPh) PASAL 21 UNTUK TAMBAHAN PENGHASILAN PEGAWAI NEGERI SIPIL DI DINAS TENAGA KERJA KOTA MANADO - Mumu, Ablessy; Latulola, Anatasya; Rondonuwu, Sintje (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
In improving the quality and performance of civil servants in government agencies, a rule is made regarding the addition of employee income which is income outside of salary which must be subject to income taxÂ  article 21. This research aims to examine the calculation of income tax article 21 for civil servants civil in Dinas Tenaga Kerja Manado society is in accordance with applicable regulations, also aims to add insight into aspects of taxation, especially in calculating income tax article 21. The method used is representative of the quantitative data obtained from the object of service. While the technique of application is to collect quantitative data in the form of numbers and calculations, then based on these data testing is done in order to convince a theory issued.Keywords : Income tax, Additional income